Intracellular cleavage and ligation of hepatitis delta virus genomic RNA: regulation of ribozyme activity by cis-acting sequences and host factors. - Lazinski, D W (1995)
During replication, a ribozyme within the genomic RNA of hepatitis delta virus cleaves multimeric precursors to release a unit-length linear intermediate. Intramolecular ligation of this intermediate produces the circular genomic RNA. Although one copy of the ribozyme is reconstituted by such ligation, it does not subsequently cleave and destroy the circular conformation. We have identified cis-acting attenuator sequences that prevent self-cleavage of the circular product by base pairing with and inactivating the ribozyme. Furthermore, we have shown that during the initial processing of the multimeric precursor RNA, host-specific factors activate the ribozyme by preventing its association with the attenuator sequences. Thus, we demonstrate a novel switching mechanism that regulates ribozyme activity inside the cell.